mūlāḥaẓāt mutammamah li-dirāsah manḥūtah ’Atlanta - Tarūkāy, Mādalīn
Madeleine Trokay, Supplementary Observations for the Study of the Atlanta Sculpture; ersch. 1986?; in arabic, translated and abridged by Baš?r Zuhd?.